2005
DOI: 10.1007/s11746-005-1051-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of randomization on the oxidative stability of corn oil

Abstract: Randomized corn oil TAG oxidized much faster than natural oil, but after purification with alumina, they oxidized at the same rate. We showed that this effect could not be attributed to a difference in total tocopherols in the randomized and natural oils. Polar material recovered from the alumina treatment was fractionated by TLC, and a pro-oxidant effect was found in the fractions containing MAG and DAG. However, MAG and DAG, although mild pro-oxidants, could not account for the prooxidant effect generated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 19 publications
0
19
1
Order By: Relevance
“…Therefore, the soybean oil after removal of tocopherols is a good model for studying antioxidant effects because of its richness in double bonds. Our previous test with the same procedure showed that at least 99% of the naturally occurring tocopherols were removed by purification with activated alumina (28).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the soybean oil after removal of tocopherols is a good model for studying antioxidant effects because of its richness in double bonds. Our previous test with the same procedure showed that at least 99% of the naturally occurring tocopherols were removed by purification with activated alumina (28).…”
Section: Resultsmentioning
confidence: 99%
“…Mistry and Min 21 reported that MAG and DAG acted as pro-oxidants at concentrations of 0.25-0.5% at 55 • C in purified soybean oil. Wang et al 17 reported that polar material recovered from randomised corn oil by using an alumina column after TLC fractionation had a pro-oxidant effect. Therefore, we purified SLs and SBO using a silica column.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the addition of a small amount of metal ions significantly decreased the oxidative stability index (OSI) of randomised corn oil. 17 Akoh and Moussata 16 reported that SL which was produced by enzymatic interesterification of canola oil or fish oil and CA was less stable than the unmodified canola or fish oil. In contrast, Kimoto et al 18 determined that enzymatic interesterification with random lipase caused an increase of oxidative stability of fish oil because the level of highly unsaturated TAGs was decreased.…”
Section: Induction Timementioning
confidence: 99%
“…Lecithin, 5 g, was first subjected to saponification by following AOCS official method Ca 6a-40 (10), and the unsaponifiable matter was extracted. The extract was used for HPLC quantification for tocopherols.…”
Section: Methodsmentioning
confidence: 99%